The Meryl Streep movie club - March, Mia (Gallery Books, 2012)
"Two sisters and the cousin they grew up with after a tragedy are summoned home to their family matriarch's inn on the coast of Maine for a shocking announcement. Suddenly, Isabel, June, and Kat are sharing the attic bedroom-and barely speaking. But when innkeeper Lolly asks them to join her and the guests in the parlor for weekly Movie Night-it's Meryl Streep month-they find themselves sharing secrets, talking long into the night-and questioning everything they thought they knew about life, love, and one another."--P. [4] of cover.